U.S. Investors' Emerging Market Equity Portfolios : A Security-Level Analysis - Warnock, Francis (IMF Working Papers; Working Paper ;, 2003)
We analyze a unique data set and uncover a remarkable result that casts a new light on the home bias phenomenon. The data are comprehensive, security-level holdings of emerging market equities by U.S. investors. We document, as expected, that at a point in time U.S. portfolios are tilted towards firms that are large, have fewer restrictions on foreign ownership, or are cross-listed on a U.S. exchange. The size of the cross-listing effect is striking. In contrast to the well-documented underweighting of foreign stocks, emerging market equities that are cross-listed on a U.S. exchange are incorporated into U.S. portfolios at full international capital asset pricing model (CAPM) weights. Our results suggest that information asymmetries play an important role in equity home bias and that the benefits of international risk sharing are limited to select firms.